PENYULUHAN PENDIDIKAN SEKS KEPADA SISWA-SISWI SD KANISIUS SENGKAN YOGYAKARTA - Elisabeth Desiana Mayasari (Universitas Sanata Dharma, 2018)
Sexual education is importantly needed in giving students adequate knowledge on how important it is to take care of their reproductive organs and to raise an understanding of moral values about sexuality problems. In the other hand, as a fact, teachers and parents often give abstract explanation when children ask about sexuality. Based on the data from Komnas Perlindungan Anak, the fact shows that in January to June 2013, there were 1.032 violence cases done to children. These cases were divided into two: 294 physical violence cases and 241 psychological violence cases. The aim of this social service program was to conduct a practice of sexual education counseling for students in SD Kanisius Sengkan. The sexual education counseling process was done through Ignatian Pedagogy Paradigm (reflective) learning process. The results from the sexual education counseling done to students in SD Kanisius Sengkan showed that 69% of male and female students understood the sexual education given and knew how to take care of their body, 100% of male students and 94% of female students were able to take care of their body after they were given the sexual education counseling, 69% of male students and 80% of female students got the benefit from the sexual education counseling conducted.